2003
DOI: 10.1002/cne.10825
|View full text |Cite
|
Sign up to set email alerts
|

Timing of neuronal and glial ultrastructure disruption during brain slice preparation and recovery in vitro

Abstract: Hippocampal slices often have more synapses than perfusion-fixed hippocampus, but the cause of this synaptogenesis is unclear. Ultrastructural evidence for synaptogenic triggers during slice preparation was investigated in 21-day-old rats. Slices chopped under warm or chilled conditions and fixed after 0, 5, 25, 60, or 180 minutes of incubation in an interface chamber were compared with hippocampi fixed by perfusion or by immersion of the whole hippocampus. There was no significant synaptogenesis in these slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 62 publications
(81 reference statements)
12
115
0
2
Order By: Relevance
“…Second, whereas measuring the AD onset by field recording only gives data on the time of the AD, using whole-cell clamping enables us to examine, in addition, the time course of the pre-AD and post-AD current changes generated by ischemia and to monitor exocytotic transmitter release as miniature synaptic currents. Hippocampal slices, 225 m thick, were prepared from postnatal day 12 (P12) rats (or in some experiments, P28 rats, as noted in Results) as described by , with Na-kynurenate (1 mM) in the slicing solution to block glutamate receptors, and were recorded 2-5 h after slicing, at which time glycogen levels should have almost completely recovered from the slicing process (Fiala et al, 2003). Recordings were at 33 Ϯ 1°C, with slices submerged in flowing solution (10 ml/min), which normally contained the following (in mM): 126 NaCl, 24 NaHCO 3 , 1 NaH 2 PO 4 , 2.5 KCl, 2 MgCl 2 , 2.5 CaCl 2 , and 10 glucose, bubbled with 95% O 2 /5% CO 2 , pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…Second, whereas measuring the AD onset by field recording only gives data on the time of the AD, using whole-cell clamping enables us to examine, in addition, the time course of the pre-AD and post-AD current changes generated by ischemia and to monitor exocytotic transmitter release as miniature synaptic currents. Hippocampal slices, 225 m thick, were prepared from postnatal day 12 (P12) rats (or in some experiments, P28 rats, as noted in Results) as described by , with Na-kynurenate (1 mM) in the slicing solution to block glutamate receptors, and were recorded 2-5 h after slicing, at which time glycogen levels should have almost completely recovered from the slicing process (Fiala et al, 2003). Recordings were at 33 Ϯ 1°C, with slices submerged in flowing solution (10 ml/min), which normally contained the following (in mM): 126 NaCl, 24 NaHCO 3 , 1 NaH 2 PO 4 , 2.5 KCl, 2 MgCl 2 , 2.5 CaCl 2 , and 10 glucose, bubbled with 95% O 2 /5% CO 2 , pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, quantitative three‐dimensional EM data have suggested that cellular organelles associated with Ca 2+ signaling indeed tend to occur inside astroglia at some distance from the nearby excitatory synapses (Patrushev et al, 2013). However, PAPs do seem to contain individual ribosomes and glycogen granules, together with actin and actin binding proteins (Bernardinelli et al, 2014a; Derouiche and Frotscher, 2001; Fiala et al, 2003; Molotkov et al, 2013; Safavi‐Abbasi et al, 2001; Seidel et al, 1995). Moreover, recent results illustrate that despite general believe, fine astrocyte processes do contain some types of calcium stores and sinks as seen with EM (Lovatt et al, 2007; Sahlender et al, 2014; Volterra et al, 2014).…”
Section: Molecular Makeup Of Perisynaptic Astroglial Processes: Majormentioning
confidence: 99%
“…If microtubules transiently appear in dendritic spines [Westrum and Gray, 1977;Westrum et al, 1980;Chicurel and Harris, 1992;Fiala et al, 2003], the interaction between these microtubules and the PSD might serve as a means to induce the disintegration of the PSD from a simple, un-perforated shape to the variously segmented shapes as found in the brain [Hering and Sheng, 2001;Toni et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Chicurel and Harris [1992] reported the presence of microtubules in the branched dendritic spines of rat hippocampal CA3 neurons. When hippocampal slices prepared at 08C were warmed up to 378C, a transient appearance of microtubules in the dendritic spines of CA1 neurons was found at first [Fiala et al, 2003]. These observations seem to suggest that unstable microtubules may be formed transiently in some dendritic spines.…”
Section: Introductionmentioning
confidence: 95%